The intravenous glucose tolerance and postprandial glucose tests may present different responses in the evaluation of obese dogs. - Brunetto, Márcio Antonio [UNESP]; Sá, Fabiano César; Nogueira, Sandra Prudente; Gomes, Márcia de Oliveira Sampaio; Pinarel, Amanda Gullo; Jeremias, Juliana Toloi; de Paula, Francisco José Albuquerque; Carciofi, Aulus Cavalieri (My University, 2011)
The present study compared the intravenous glucose tolerance test (IVGTT) and the glucose postprandial response (GPPR) test for the evaluation of glucose metabolism in obese dogs. A total of ten owned obese dogs (body condition score (BCS) of 9; fat mass, 45.7 (sem 1.51) %) were used. These dogs had their weight reduced by 20 % (BCS, 8; fat mass, 33.5 (SEM 1.92) %; P < 0.001), designated as weight-reduced (WR) group. A control group of ten Beagle dogs was also included (BCS, 4.5; fat mass, 18.3 (SEM 1.38) %; P < 0.01). Glucose tolerance was measured by two methods: IVGTT (infusion of 0.5 g of glucose/kg body weight) and GPPR (consumption of cooked rice to achieve 6 g of starch/kg body weight). When using the IVGTT, the area under the curve (AUC) for glucose and maximum glycaemia were higher for obese dogs compared with controls (P < 0.05), with intermediate results for the WR group (P>0.05). Basal insulin, insulin response peak, insulinogenic index and the AUC for insulin increment from 0 to 15 min and from 60 to 120 min were higher for the obese group (P < 0.05), while the WR group and control dogs showed similar results (P>0.05). When using the GPPR test, the AUC for insulin increment from 0 to 120 min was higher for the obese group compared with the control group (P < 0.05) and intermediate for the WR group (P>0.05). However, the AUC for insulin increment from 120 to 360 min was similar between the obese and WR groups (P>0.05), while it was lower for the control group (P < 0.05). The IVGTT showed that the loss of 20 % body weight resulted in an improvement of glucose control with reduced insulin secretion, and these same WR dogs showed higher insulin secretion with values similar to those of obese dogs when the GPPR test was used.